HTLV seroprevalence in people using HIV pre-exposure prophylaxis in England. Issue 3 (March 2023) - Bradshaw, Daniel; Khawar, Arham; Patel, Poorvi; Tosswill, Jennifer; Brown, Colin; Ogaz, Dana; Mason, Emily; Osman, Roeann; Mitchell, Holly; Dosekun, Olamide; Peris, Borja Mora; Pickard, Graham; et al.
Highlights: First study to evaluate the potential risk of HTLV transmission amongst people who use HIV-PrEP. No (0/2015) HTLV-1/HTLV-2 cases found in people who use HIV-PrEP in England. Similar studies are needed amongst HIV-PrEP uses elsewhere, particularly in HTLV-1 endemic settings. Summary: Objectives: HTLV-1 is predominantly a sexually-transmitted infection but testing is not mentioned in HIV-PrEP guidelines. We ascertained HTLV-1/HTLV-2 seroprevalence amongst HIV-PrEP users in England. Methods: An unlinked anonymous seroprevalence study. Results: Amongst 2015 HIV-PrEP users, 95% were men, 76% of white ethnicity and 83% had been born in Europe. There were no HTLV-1/HTLV-2 seropositive cases (95% confidence interval 0% – 0.18%). Conclusions: There were no HTLV positive cases, likely reflecting the demographic of mostly white and European-born individuals. Similar studies are needed worldwide to inform public health recommendations for HIV-PrEP using populations, particularly in HTLV-endemic settings.